2013
DOI: 10.5114/pjp.2013.34604
|View full text |Cite
|
Sign up to set email alerts
|

Pure tocotrienol concentrate protected rat gastric mucosa from acute stress-induced injury by a non-antioxidant mechanism

Abstract: Stress has been implicated as a risk factor of various major health problems, such as stress-induced gastric mucosal injury. This study was performed to investigate the action of a pure preparation of tocotrienol (T3) concentrate, made up of 90% δ-tocotrienol and 10% γ-tocotrienol, on gastric injury of rats induced by water-immersion restraint stress (WIRS). Fourteen male Sprague-Dawley rats (200-250 g) were divided into two equal groups: a control group and a treated group. The treatment group received T3 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Research has shown the importance of maintaining a balance between the destructive and the protective capacity of the gastric mucosa to prevent formation of such mucosal injuries [ 2 , 4 ]. Supplementation with vitamin E such as tocopherol and tocotrienol have been shown to reduce the formation of stress-induced gastric lesions as reported in previous studies [ 24 , 25 ]. The findings observed in the study by Ibrahim et al showed a significant reduction in mean gastric lesions in rats supplemented with palm-vitamin E (which contains 70% tocotrienol) and α-tocopherol (60 mg/kg body weight for 28 days).…”
Section: Discussionmentioning
confidence: 52%
“…Research has shown the importance of maintaining a balance between the destructive and the protective capacity of the gastric mucosa to prevent formation of such mucosal injuries [ 2 , 4 ]. Supplementation with vitamin E such as tocopherol and tocotrienol have been shown to reduce the formation of stress-induced gastric lesions as reported in previous studies [ 24 , 25 ]. The findings observed in the study by Ibrahim et al showed a significant reduction in mean gastric lesions in rats supplemented with palm-vitamin E (which contains 70% tocotrienol) and α-tocopherol (60 mg/kg body weight for 28 days).…”
Section: Discussionmentioning
confidence: 52%
“…After 1 week‐adaptation, these rats were randomly enrolled into four groups, were treated for 14 days by gavage, as follows: Control group ( n = 6:rats received 1 ml of corn oil containing 10% DMSO; Delta group ( n = 6); rats treated with Delta (60 mg/ kg of body weight) dissolved in DMSO and later scaled to the required volume with corn oil; OTA group ( n = 6): rats treated with OTA (0.5 mg/kg of body weight) dissolved in 10% DMSO and then scaled to required volume with corn oil; OTA plus Delta group ( n = 6): rats treated with Delta (60 mg /kg of body weight) plus OTA (0.5 mg/kg kg of body weight). The doses and times of Delta and OTA administration were chosen according to previous experiments (Ciarcia et al, ; Rodzian, Aziz Ibrahim, Nur Azlina, & Nafeeza, ). The rats were weighed at baseline (before receiving the first dose), five, 10, and at the end of the 14 days treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Stress reduced the level of PGE 2 in the stomach at least by half of its normal level, which was accompanied by formation of lesions [226][227][228]. Interestingly, Rodzian et al (2013) found that the supplementation annatto T3, which mainly contains δT3 isomer, suppressed gastric PGE 2 level [229]. On the other hand, palm pure T3 mixture was able to protect the gastric mucosa with the elevation of PGE 2 level, which was associated with an increased in cyclooxygenase-1 (COX-1) expression [221].…”
Section: Effects Of Tocotrienol On Peptic Ulcersmentioning
confidence: 96%